TRADISI BATIMBANG SALAH DI NAGARI SALIMPEK - Vinni Annisa Putri (Jurnal Elektronik WACANA ETNIK, 2017)
This article is a description of Batimbang Salah tradition in Nagari Salimpek Lembah Gumanti, Solok Regency. Batimbang Salah is a customary law procession carried out if there are people breaking adat. The aim is to provide punishment and provide a deterrent effect to the Salimpek community.The Batimbang Salah tradition is part of the application of customary law in the Minangkabau region, especially for the Salimpek community. This tradition is one form of tradition that is important to maintain. This Batimbang Salah tradition is still relevant to maintain its existence in the life of the Minangkabau people today.Keywords: batimbang salah, customary law, Minangkabau, Salimpek